Description of Moca austrasinensis sp. nov., with the first record of Imma lathidora Meyrick, 1914 from mainland China (Lepidoptera, Immidae) - Huang, Si-Yao; Yu, Tian-Tian; Fan, Xiao-Ling; Wang, Min (Zootaxa, 2019)
Some new information on a poorly studied lepidopterous family, Immidae Heppner, 1977, is reported from Guangdong Province, in the southern part of mainland China. A new species, viz. Moca austrasinensis Huang & Wang sp. nov. is described from Mt. Wutong, Shenzhen. Imma lathidora Meyrick, 1914 is recorded in Mt. Nankun, Huizhou, representing the first record from mainland China. Adults and male genitalia of the species mentioned are illustrated.